1986
DOI: 10.1016/0042-6989(86)90078-7
|View full text |Cite
|
Sign up to set email alerts
|

Optic flow

Abstract: This paper offers a quick review of the subject of "optic flow" in its conceptual and computational aspects. The theory is evaluated in terms of possible applications in the neurophysiology and experimental psychology of spatial sensorymotor behaviour and perception. The problem of which kind of detector is suited to extract various aspects of optic flow is given special attention. It is shown that the possibilities are actually much more various than is reflected in the current (even the frankly speculative) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
435
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 729 publications
(452 citation statements)
references
References 30 publications
5
435
0
1
Order By: Relevance
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 .…”
Section: Review Insightmentioning
confidence: 99%
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 .…”
Section: Review Insightmentioning
confidence: 99%
“…
articlesThe optic flow 1 that is generated when a person moves through the environment can be locally decomposed into several basic components, including radial, circular, translation and sheer motion 2,3 . Neurons in the dorsal portion of the medial superior temporal cortex (MSTd) of macaque monkeys respond selectively to these components, alone or in combination [4][5][6][7] .
…”
mentioning
confidence: 99%
“…Several algorithms based on the rigidity assumption for special cases, such as planes, have been developed (Mayhew and Longuet-Higgins 1982). Psychophysical results show that human performance on some sfm tasks is at least broadly consistent with predictions based on the rigidity assumption (Wallach and O'Connell 1953;Koenderik 1986). More recent affine models are based only on local velocity information, rather than on the entire optic flow field, to account for human perception (Todd and Bressan 1990;Todd and Norman 1991).…”
Section: Introductionmentioning
confidence: 80%